Measurement of the W boson helicity in top quark decays at D0 - Abazov, V. M. (2007)
We present a measurement of the fraction f+ of right-handed W bosons produced in top quark decays, based on a candidate sample of tt̄ events in the +jets and dilepton decay channels corresponding to an integrated luminosity of 370pb-1 collected by the D0 detector at the Fermilab Tevatron pp̄ Collider at s=1.96TeV. We reconstruct the decay angle θ* for each lepton. By comparing the cos θ* distribution from the data with that for the expected background and signal for various values of f+ (where we assume that the fraction of longitudinally-polarized W bosons has the standard model value of 0.70), we find f+=0.056±0.080(stat)±0.057(syst) (f+<0.23 at 95% C.L.), consistent with the standard model prediction of f+=3.6×10-4. © 2007 The American Physical Society.